Linking Mechanisms in the Intergenerational Transmission of Mental Health: The Role of Sex in Parent–Adolescent Dynamics - Hye-Jung Yun; Jungyeong Heo; Cynthia B. Wilson (Children)
Background/Objectives: This study addresses the significance of mental health concerns by examining the intergenerational transmission of mental health between parents and adolescents. It investigates the serial mediating effects of family resilience, adolescents’ adverse childhood experiences (ACEs), and their ability to flourish in the transmission of mental health from parents to adolescents, with a focus on sex differences. Methods: This study used a sample of 54,434 adolescents aged 12–17 from the 2016–2020 National Survey of Children’s Health (NSCH). Mothers reported on their mental health status and family resilience, and adolescents’ ACEs, flourishing, and mental health problems including depression and anxiety. Serial mediation models were used to assess the hypotheses. Results: The findings revealed that better parental mental health status was associated with fewer mental health problems in adolescents, with significant sex differences observed in these associations. Specifically, in both maternal and paternal models, better parental mental health was linked to higher family resilience, which was associated with fewer ACEs, greater flourishing, and ultimately fewer adolescent mental health problems. Furthermore, maternal mental health had a stronger association with daughters’ mental health, while paternal mental health more strongly influenced sons’. Conclusions: These results highlight the importance of targeted prevention and clinical interventions to disrupt the intergenerational transmission of mental health issues.